Yield limitations and production zones of rainfed grain sorghum in the Southern Great Plains - Sexton-Bowser, Sarah (My University, 2024)
The Southern Great Plains is a semi-arid cropping region in which two of the primary concerns for local farmers are yield level and yield stability. In this thesis we investigated three central questions related to rainfed cropping systems in the Southern Great Plains. Our first question was i) Why are grain sorghum yields stagnating in Kansas? The yield gap for grain sorghum was estimated using an extensive dataset of crop performance trials, yield contest data, and county-level survey yield data totaling 2997 site-years. State-level yield was 4.7 Mg ha-1, which represents 77% of the attainable yield and 49% of the water-limited yield potential. Sorghum grain yields in Kansas rainfed systems appear to be stagnating due to a small gap between current and maximum attainable yield and a generalized statewide shift in planting area to environments with greater water deficit. Our second question was ii) What are the major homogeneous crop production agro-zones for the state of Kansas? We delineated the state of Kansas using a hierarchical clustering method which first consisted of classifying macro agro-zones based on climate features, and then each macro area was further divided into micro areas based on soil physical features. We identified three optimal clusters of relatively homogeneous climatic conditions that partitioned the state into northwest, southwest, and east, each with two nested micro-AZs based on soil physical properties. Our final question was iii) Has maize surpassed grain sorghum in its ability to yield under drought conditions? We evaluated county-level non-irrigated yield reports from USDA-RMA relative to USDA-NASS for the period of 2019 to 2023. The use of a county-report with combined irrigated and non-irrigated practices resulted in a four-fold overestimation of maize yield advantage to grain sorghum. According to our new findings, grain sorghum maintains a persistent yield advantage to maize in some water-limited environments.
Keywords: Grain sorghum; Yield gap; Agrozone; Great Southern Plains crop production